The Optimal Permissible Placement by the Height of the Transitive Oriented Treecontaining One Vertex of Branching - Khachaturyan, Armen (Mathematical Problems of Computer Science, 2021)
In this paper we consider the optimal permissible placement by the height of the following type of transitive oriented graphs (the height of the vertex is the number of the arcs passing through the vertex): the graph consists of chains of quantity s ≥ 2 branching after the end of the chain. The problem was solved by the algorithm of s log s complexity.